P226 DYNAMO Covid-19. Dynamic assessment of multi organ level dysfunction in patients recovering from Covid-19: insulin resistance and metabolic flexibility. (11th November 2022) - Gutpa, A; Nicholas, R; McGing, JJ; Mougin, O; Bradley, CR; Nixon, AV; Mallinson, JE; Bonnington, J; McKeever, TM; Hall, IP; Lord, JM; Evans, RA; et al.
Abstract : Introduction: Initial acute hyperglycaemia is reported in patients during hospitalisation with SARS-CoV-2 infection. However, it is unclear what maladaptations occur long-term. Whole-body insulin sensitivity and metabolic flexibility were assessed alongside whole-body and regional fat content to provide insight of metabolic health status in recovering patients. Methods: Adults were recruited at 5–7 months following hospital discharge for severe SARS-Cov2 infection (n=21), along with control volunteers (n=10) of a similar age, gender, ethnicity and BMI. Indirect calorimetry was conducted before and during an oral glucose tolerance test (OGTT) to assess metabolic flexibility [Δ respiratory exchange ratio (RER) from fasting to peak]. In conjunction, regular arterialised venous bloods were taken from a retrograde cannula over a 3-hour period to determine blood glucose and serum insulin. At separate visits (within 2 weeks), dual energy X-ray absorptiometry measured whole-body fat fraction, whilst 1 H Magnetic Resonance Spectroscopy (MRS) quantified intra and extra-myocellular lipid fractions (IMCL and EMCL) in the thigh muscle and MR Imaging using a mDIXON scan identified subjects with fatty liver (fat fraction> 5.6%). Average daily activity over a 7-day period was measured using an accelerometer. Data are Non-parametric: median(IQR), parametric: mean(SD) and categorical: n(%). Results: The OGTT serum insulin response was greater in patients (P) than controls (C) ( figure 1b ), but the blood glucose ( figure 1a ) and RER responses [P: 0.08(0.07) vs C: 0.13(0.07), p=0.1] were not. Patients had a lower average daily step count [P: 3, 626(2, 385–6, 337) steps vs C: 7, 670(5, 111–10, 074), p=0.07] and more had a fatty liver [P: 13(68%) vs C: 3(30%), p=0.048]. Whole-body fat fraction [P: 38.3(6.8)% vs C: 37.4(9.6)%, p=0.8] and IMCL:EMCL [P: 0.45(0.28) vs C: 0.67(0.42), p=0.1] were not different. Physical activity and liver fat were independent factors for insulin resistance in a multivariate regression model. Conclusion: Patients recovering from severe Covid-19 have worse insulin sensitivity compared to controls, but similar metabolic flexibility. Physical inactivity and liver adiposity may play a role in these observations. Funding: NIHR Nottingham BRC (NoRCoRP), PHOSP UKRI, Nottingham Hospitals Charity, University of Nottingham alumni donation.